2016
DOI: 10.4172/2254-609x.100039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucosinolates Rich Broccoli extract against Triazophos induced Toxicity in Wistar Rats

Abstract: Background: Triazophos (TZ), an organophosphate (OP) pesticide, is widely used as non-systemic broad spectrum pesticide against insect pests. OPs, apart from neurotoxicity and neurobehavioral changes in animals, have been shown to induce oxidative stress (OS) by generating elevated levels of reactive oxygen species (ROS) which culminates into oxidative stress (OS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…25 These findings agree with other studies in which Brassica phytochemicals showed antioxidant effects and decreased oxidative damage. 43,44 Experimental Chemicals All the reagents used were of the highest grade and were purchased from Sigma-Aldrich (St Louis, MO, USA), Carlo Erba (Milan, Italy), Bio-Rad Laboratories (Segrate, Italy) and GE Healthcare (Uppsala, Sweden).…”
Section: Effect Of Diet On Anti-inflammatory Factorsmentioning
confidence: 99%
“…25 These findings agree with other studies in which Brassica phytochemicals showed antioxidant effects and decreased oxidative damage. 43,44 Experimental Chemicals All the reagents used were of the highest grade and were purchased from Sigma-Aldrich (St Louis, MO, USA), Carlo Erba (Milan, Italy), Bio-Rad Laboratories (Segrate, Italy) and GE Healthcare (Uppsala, Sweden).…”
Section: Effect Of Diet On Anti-inflammatory Factorsmentioning
confidence: 99%
“…Hasil penelitian Sharma & Sangha (2016) menyebutkan bahwa pemberian ekstrak brokoli yang mengandung glukosinolat menyebabkan penurunan stress oksidatif pada tikus yang diberi paparan toksisitas triazophos. Hasil penelitian tersebut menujukkan pemberian ekstrak brokoli sebanyak 20 µmol dan 30 µmol dapat menurunkan kadar MDA tikus putih betina secara signifikan dibandingkan dengan tikus yang diberi perlakuan triazophos.…”
Section: Kadar Malondialdehid (Mda)unclassified
“…Loss of cholinergic markers enzymes such as AChE is correlating with the degree of cognitive and loss of this enzymes is considered the most severe and the earliest of the biochemical changes to occur. Chronic Aluminium exposure has choline toxic effects and significant reduction of AChE activity is seen with Aluminium [45][46][47]. Aluminum can result in the production of free radicals which lead to oxidative damage, and this may be responsible for the decreased AChE enzyme activity.…”
Section: Treatedmentioning
confidence: 99%